The Effect of Advertisement, Word of Mouth, and Brand Awareness towards Buying Decision on "Ruang Guru Apps" in SMU Negeri XYZ Surakarta - Andri Astuti Itasari; Nurnawati Hindra Hastuti (Journal of Consumer Sciences, 2023)
Besides studying at school, online tutoring is a non-formal method of education delivery. One online tutoring is Ruang Guru's app, and it is still among competitors such as Zenius, tutoring conventional, and others. This research focuses on Ruang Guru's apps, which have always existed among students in Surakarta until now. This research uses descriptive quantitative. This research analyzes advertisements, word of mouth, and brand awareness toward buying Decision on Ruang Guru apps for students. The population is all SMU Negeri XYZ Surakarta students, with a total of 1.191 students, and about 100 students were selected as the respondent through a random sampling technique. Data collection techniques using questionnaires as primary data and documents from journals and books as secondary data. Data were analyzed using the Structural Equation Modelling - Partial Least Square (PLS). This research shows that advertisement and word of mouth significantly positively affect brand awareness. In addition, advertisement, word of mouth, and brand awareness positively affect buying decisions. Furthermore, advertisement and word of mouth significantly affect buying decisions through brand awareness. Therefore, it is suggested that companies continue to increase word-of-mouth promotions and advertisements related to consumer behavior in purchasing decisions.